TO EVALUATE THE NEUROPROTECTIVE ACTIVITY OF STRAWBERRY AND BLUEBERRY EXTRACT IN MPTP-INDUCED PARKINSONISM IN MICE - KUMAR, LALIT; MALHOTRA, MEENAKSHI; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2026)
Objective: This study aimed to evaluate the neuroprotective effects of ethanolic extracts of strawberry and blueberry in an MPTP-induced mouse model of Parkinsonism. Methods: Swissmice (30–35 g) were divided into five groups: control, MPTP-treated, Syndopa (Levodopa+Carbidopa)-treated, low-dose extract-treated, and high-dose extract-treated groups. Parkinsonism was induced using MPTP (20 mg/kg) for seven consecutive days. Mice were then administered either Syndopa (10 mg/kg) or strawberry and blueberry extracts at low (100 mg/kg) or high (200 mg/kg) doses for Seven days. Behavioural assessments, including the Rotarod test, Grip test/Hang test, Open-field test, Actophotometer test, Forced Swim test, Elevated plus maze test, and Catalepsy/Wooden bar test, were conducted to evaluate motor function, anxiety-like behaviour, and catalepsy. Results: MPTP administration led to significant motor impairments, increased catalepsy, and reduced locomotor activity. Treatment with strawberry and blueberry extracts significantly improved motor coordination, reduced cataleptic symptoms, and enhanced locomotor activity in a dose-dependent manner. The observed neuroprotective effects were comparable to those of Syndopa (Levodopa+Carbidopa)-treated, suggesting that bioactive compounds in these fruits may mitigate neurodegeneration. Conclusion: The results support the potential of strawberry and blueberry extracts as natural therapeutic agents in Parkinson’s disease. Their antioxidant and neuroprotective properties warrant further investigation into the underlying mechanisms and potential clinical applications in PD management.